2022
DOI: 10.3389/fnagi.2022.890958
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmune Crosstalk Between the Peripheral and the Central Immune System in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal disease characterized by the degeneration and death of motor neurons. Systemic neuroinflammation contributes to the pathogenesis of ALS. The proinflammatory milieu depends on the continuous crosstalk between the peripheral immune system (PIS) and central immune system (CIS). Central nervous system (CNS) resident immune cells interact with the peripheral immune cells via immune substances. Dysfunctional CNS barriers, including the blood–brain barrier, and blood–spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 126 publications
(132 reference statements)
1
13
0
Order By: Relevance
“…Interleukin-1 (IL1) that is secreted by activated microglia in context with PD pathogenesis [ 63 ] is a critical cytokine for Th17 cell differentiation [ 64 , 65 ]. As shown for other neurodegenerative diseases [ 66 ] a crosstalk between the brain and periphery may provide a potential explanation for our findings of increased TH17 counts in PD peripheral blood samples. In addition, we found an increased prevalence of a specific subtype of IL-17 producing gamma delta T cells in PD patients.…”
Section: Discussionsupporting
confidence: 72%
“…Interleukin-1 (IL1) that is secreted by activated microglia in context with PD pathogenesis [ 63 ] is a critical cytokine for Th17 cell differentiation [ 64 , 65 ]. As shown for other neurodegenerative diseases [ 66 ] a crosstalk between the brain and periphery may provide a potential explanation for our findings of increased TH17 counts in PD peripheral blood samples. In addition, we found an increased prevalence of a specific subtype of IL-17 producing gamma delta T cells in PD patients.…”
Section: Discussionsupporting
confidence: 72%
“…Considerable evidence has revealed the presence of peripheral immunity abnormalities in the progress of ALS after diagnosis 2,35 . The peripheral immune system includes the innate immune system, with neutrophils at its core components, and the adaptive immune system, with lymphocytes at its core components.…”
Section: Discussionmentioning
confidence: 99%
“…However, the viewpoint was updated with the increasing number of studies, which revealed a functional crosstalk between peripheral immune cells and the CNS. 2 The peripheral immune system includes the innate immune system, with neutrophils as its core component, and the adaptive immune system, with lymphocytes as its core component. Different immune cell subpopulations display different functions in ALS disease progression; T regulatory cells (Tregs) appear to be protective, 3 whereas neutrophils, inflammatory monocytes, and CD8 + T cells may be destructive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence implicates neuroimmune crosstalk between the peripheral immune system (PIS) and central immune system (CIS) in ALS, cooperatively contributing to the death of motor neurons (Yu et al, 2022). An increased infiltration of peripheral immune cells into the spinal cord and motor cortex of patients with ALS has been observed, which, together with activated microglia and astrocytes, constitute a pro-inflammatory immune microenvironment (Beers and Appel, 2019).…”
Section: Introductionmentioning
confidence: 99%